Psychosocial factors associated with perceived social support in Brazilian older people - Patrão, Ana Luísa; Alves, Vicente Paulo; Neiva, Tiago Sousa (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2018)
The social support has been reported as playing an important role in the older people life due to its protection effect for health in this specific people. This paper aims to identify psychosocial predictors for perceived social support in Brazilian older people. The sample is constituted by 144 patients (M age=69.3; SD=6.61). The data were collected through a questionnaire that included sociodemographic questions and scales for psychological variables (e.g. self-efficacy) studied. Lower age, higher level of education, being married or living in a stable union, low levels or absence of depression and high levels of self-efficacy are significant predictors of perceived social support in older people who were studied. Future interventions in older people health promotion context may consider these determinants.